Indonesian Islamic Religious Education Curriculum: A Review of Compliance with Global Education Standards - Bella Nabilla; Juliani; Dea Puspita Sari; Dwi Khairunisapril; Septia Pandini (Yayasan Zia Salsabila, 2024)
This research aims to examine the suitability of the Islamic Religious Education (PAI) curriculum in Indonesia with global education standards. In the context of an increasingly integrated world, the PAI curriculum is expected to be able to reflect universal values, such as tolerance, inclusiveness, and desire, without ignoring local identity and religious values. This research uses a descriptive-analytic approach with a literature study method. The research results show that although the PAI curriculum includes several elements of global education, such as character education and strengthening moral values, there are still challenges in integrating technology, global literacy, and diversity-based education. In addition, resistance to change and limited resources are significant obstacles in implementing a curriculum that is in line with global standards. Therefore, it is necessary to develop a curriculum based on a global-local approach (glocalization), increase the capacity of educators, as well as collaborative support from the government, educational institutions, and the community. With this step, it is hoped that the PAI curriculum will be more responsive to global changes and contribute to forming a generation that is religious, tolerant, and competitive at the international level.